2007
DOI: 10.2193/2006-008
|View full text |Cite
|
Sign up to set email alerts
|

Winter Survival of Wild Turkey Females in Central Minnesota

Abstract: There is interest in expanding eastern wild turkey (Meleagris gallopavo silvestris) populations north of their current range. We hypothesized that winter survival and food availability are primary determinants in setting the northern extent of wild turkey distribution. To test our hypothesis, we translocated wild turkey females north of their present range into central Minnesota, USA, and compared survival in areas with supplemental food in the form of corn food plots versus areas with no supplemental food. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
(35 reference statements)
1
30
0
Order By: Relevance
“…We often found wintering flocks of turkeys congregating near active dairy farms, fields of standing corn or soybeans, and around corn cribs. This wintering behavior is fairly common for populations at northern latitudes and others have reported that active dairy farms where manure is regularly spread and fields of standing crops are important sources of food, especially when snow depths are >30 cm , Vander Haegen et al 1989, Kane et al 2007.…”
Section: Survival and Probable Causes Of Mortalitymentioning
confidence: 96%
“…We often found wintering flocks of turkeys congregating near active dairy farms, fields of standing corn or soybeans, and around corn cribs. This wintering behavior is fairly common for populations at northern latitudes and others have reported that active dairy farms where manure is regularly spread and fields of standing crops are important sources of food, especially when snow depths are >30 cm , Vander Haegen et al 1989, Kane et al 2007.…”
Section: Survival and Probable Causes Of Mortalitymentioning
confidence: 96%
“…For example, survival of wild turkeys in Wisconsin, Massachusetts and New York did not decrease under persistent deep snow (>25 cm; Vander Haegen et al 1988;Roberts et al 1995;Pollentier et al 2014). However, under similar snow depth (>25 cm), wild turkey survival decreased in Minnesota, Ontario, and Wisconsin (Porter et al 1983;Wright et al 1996;Nguyen et al 2003;Kane et al 2007). As winters in our study area were more severe than previous studies, it was also possible to quantify the efect of harsh winter conditions on wild turkey survival.…”
Section: Discussionmentioning
confidence: 51%
“…Wild turkeys are negatively impacted by snow depth that limits access to food (Porter et al 1980;Kane et al 2007) and precipitation during nesting that could increase predation (Roberts et al 1995). The nature of the relationship between environmental variables and wild turkey population dynamics remains poorly documented at the northern edge of their distribution (above 45° north of latitude), where climatic factors are more severe.…”
mentioning
confidence: 99%
“…Survival of eastern wild turkeys is influenced by a variety of factors. The effect of hen age and time of year (i.e., season) on survival probability has been studied extensively in the past (Vander Haegen et al, 1988;Roberts et al, 1995;Vangilder and Kurzejeski, 1995;Wright et al, 1996;Hubbard et al, 1999a;Lehman et al, 2001;Shields and Flake, 2006;Kane et al, 2007;Pollentier et al, 2014b). Additionally, climate, in the form of severe winter weather-extended periods of time with cold temperatures-and excessive rainfall during the spring and summer, impact hen survival (Austin and DeGraff, 1975;Wunz and Hayden, 1975;Porter, 1977Porter, , 1978Porter et al, 1980;Healy, 1992;Haroldson et al, 1998;Lehman et al, 2001;Shields and Flake, 2006;Kane et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For populations of wild turkeys in the Midwest, it is not uncommon for adult and yearling age-classes of eastern wild turkeys to exhibit similar survival probabilities (Roberts et al, 1995;Vangilder and Kurzejeski, 1995;Wright et al, 1996;Hubbard et al, 1999a;Shields and Flake, 2006;Kane et al, 2007;Delahunt, 2011;Pollentier et al, 2014b). However, for a population in Massachusetts, Vander Haegen et al (1988) reported higher rates of annual survival for adult hens than for yearling hens.…”
Section: Introductionmentioning
confidence: 99%